E-cigarette use, psychological distress, and daily activity participation among adults in Riyadh - Aljohani, Fenoon Abdullah; Alzubaidi, Bakriah Yahyaa; Al-Rafdan, Reem Hamdan; Alblawi, Hanan Mutiq; Alrehayan, Rama Hani; Alsenan, Ghada Abdulrahman; Almohaya, Hadeil Salman; Taha, Mona Mohamed (Frontiers in Psychiatry, 2024)
Objectives The prevalence of e-cigarettes is significantly increasing among adults as an alternative method to tobacco smoking. However, the chemical products of e-cigarettes have an influence on human general health. Therefore, this study aims to investigate the association between e-cigarette use and psychological distress as well as participation in daily activities among adults in Riyadh, Saudi Arabia. It also evaluates the demographic profile and usage patterns of e-cigarette users. Methods This cross-sectional study involved 396 e-cigarette smokers in Riyadh city. An online survey was administered, including questions about smoking patterns and the perceived effects of e-cigarettes on activities of daily living. Additionally, mental health were assessed using the Kessler 6 scale. Results Most of the participants were educated young males (61.4%). About 29.5% of the participants reported using e-cigarettes primarily to quit tobacco cigarettes. In addition, e-cigarette usage was significantly associated with lower participation in activities of daily living and higher psychological distress. Conclusion This study found that many e-cigarette users are well-educated young individuals who use e-cigarettes as a substitute for traditional cigarettes. However, the study also revealed that using e-cigarettes is associated with negative effects on smokers’ daily activities and mental health.